Preparation method and application of antioxidant spherical nano cuprous oxide

CN117843026BActive Publication Date: 2026-10-30北京天盾新材科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311541899.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-17
Publication Date
2026-10-30
Estimated Expiration
2043-11-17

AI Technical Summary

Technical Problem

暴露高表面能的晶面的氧化亚铜容易发生反应,影响材料的使用性能

Benefits of technology

[0043](1)本申请提供的抗氧化球状纳米氧化亚铜的制备方法,操作简单,反应过程不需要加热加压,有利于节能减排;采用的反应体系为水相,反应物为固相,工艺简单,反应物中铜源可完全转化为氧化亚铜,产量高,易于工业放大及规模化生产;采用的添加剂绿色环保用量小,废水中COD含量低,处理成本低;通过水合肼和添加剂的协同作用,使合成的纳米氧化亚铜结晶度高、尺寸均一、抗氧化能力强、抑菌效果佳。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117843026B_ABST
    Figure CN117843026B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of antioxidant spherical nano cuprous oxide and belongs to the technical field of nano cuprous oxide preparation. The preparation method provided by the application comprises the following steps: (1) a mixture containing a copper source, an alkali source, a reducing agent, an additive and water is subjected to reaction to obtain a solid product; and (2) the solid product is washed and dried to obtain the antioxidant spherical nano cuprous oxide. The preparation method of the antioxidant spherical nano cuprous oxide provided by the application is simple in operation, does not need heating and pressurization in the reaction process, is beneficial to energy saving and emission reduction, and through the synergistic effect of hydrazine hydrate and the additive, the synthesized nano cuprous oxide is high in crystallinity, uniform in size, strong in antioxidant capacity and good in bacteriostatic effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of nano-cuprous oxide preparation technology, and particularly relates to a method for preparing antioxidant spherical nano-cuprous oxide and its application. Background Technology

[0002] Copper-based compounds are common antibacterial agents. Their antibacterial mechanism involves the continuous release of copper ions to kill bacteria or direct contact with the bacteria. Cuprous oxide is the compound with the highest copper content among common copper compounds. Studies have shown that cuprous oxide exhibits good antibacterial effects at low concentrations, with high antibacterial activity and biocompatibility. Furthermore, biological organisms themselves readily respond to Cu... 2+ It has good regulatory ability and will not accumulate in higher organisms like other heavy metals.

[0003] Currently, common methods for preparing cuprous oxide include solid-phase methods, electrolytic methods, and liquid-phase methods. Liquid-phase reduction is one of the most commonly used methods for preparing nano-cuprous oxide. Reduction with sodium borohydride, formaldehyde, sodium sulfite, sodium hypophosphite, and ascorbic acid can produce cuprous oxide particles with various morphologies, such as octahedral, cubic, and plate-like forms. Common octahedral and cubic single-crystal morphologies of cuprous oxide typically have unique electronic structures and different surface energies on their crystal faces, resulting in different chemical reactivity in the powder. Cuprous oxide with exposed high surface energy crystal faces is prone to reaction, affecting the material's performance.

[0004] Furthermore, most of the reported preparation methods require heating, resulting in complex reaction systems and even the addition of large amounts of additives, which complicates production and post-processing, making them unsuitable for industrial production. For example, patent CN103395822A discloses a one-pot method for preparing hollow spherical cuprous oxide in a water and ethylene glycol system. This method uses a weak reducing agent (ethylene glycol), requires heating, and has a long reaction time. Patent CN 104261457A discloses a method using glucose as a reducing agent and sodium citrate and sodium carbonate to control the pH, preparing cuprous oxide with various morphologies such as cubes and spheres. Gou et al. used copper sulfate as the Cu source, added hexadecyltrimethylammonium (CTAB) activator to an aqueous solution of copper sulfate, and simultaneously added a certain amount of NaOH solution to the aqueous solution. Finally, ascorbate solution was added as a reducing agent to the reaction system. By controlling the concentration of the activator, Cu₂O nanotubes could be prepared. Summary of the Invention

[0005] To address the aforementioned technical problems, this application provides a method for preparing and applying antioxidant spherical cuprous oxide nanoparticles. By utilizing the strong reducing effect of hydrazine hydrate and adding trace amounts of additives, spherical cuprous oxide nanoparticles with strong oxidation resistance and antibacterial properties are prepared. The preparation method described in this application is carried out at room temperature (10-35℃) and normal pressure, the reaction system is aqueous, and it has low energy consumption, high yield, and simple subsequent processing, making it easy to carry out large-scale production.

[0006] To achieve the above-mentioned objectives, this application provides the following technical solution:

[0007] On the one hand, this application provides a method for preparing antioxidant spherical cuprous oxide nanoparticles, comprising the following steps:

[0008] (1) A mixture containing a copper source, an alkali source, a reducing agent, an additive, and water is reacted to obtain a solid product;

[0009] (2) The solid product is washed and dried to obtain the antioxidant spherical nano cuprous oxide.

[0010] Optionally, in step (1), the reducing agent includes hydrazine hydrate.

[0011] Optionally, the molar ratio of the copper source to the reducing agent is 1:0.25 to 1, wherein the number of moles of the copper source is calculated as the number of moles of copper ions, and the number of moles of the reducing agent is calculated as the number of moles of the substance itself.

[0012] Optionally, the molar ratio of the copper source to the reducing agent is independently selected from any value among 1:0.25, 1:0.5, 1:0.75, 1:1, or any range between two of them.

[0013] Optionally, in step (1), the copper source is a divalent copper source;

[0014] The divalent copper source includes copper sulfate, copper nitrate, or copper chloride.

[0015] Optionally, the molar concentration of the copper source is 0.1 to 1.0 mol / L.

[0016] Optionally, the molar concentration of the copper source is independently selected from any value or a range between 0.1 mol / L, 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, and 1.0 mol / L.

[0017] Optionally, in step (1), the alkali source includes sodium hydroxide, potassium hydroxide, ammonia, or sodium carbonate.

[0018] Optionally, the molar concentration of the alkali source is 0.1 to 0.5 mol / L.

[0019] Optionally, the molar concentration of the alkali source is independently selected from any value of 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, or any range between the two.

[0020] Optionally, in step (1), the additive includes at least one of glucose, sucrose, starch, sodium citrate, and sodium acetate.

[0021] Optionally, the molar ratio of the copper source to the additive is 20 to 100:1, wherein the number of moles of the copper source is calculated as the number of moles of copper ions, and the number of moles of the additive is calculated as the number of moles of the substance itself.

[0022] Optionally, the molar ratio of the copper source to the additive is independently selected from any value of 20:1, 40:1, 60:1, 80:1, 100:1 or any range between the two.

[0023] Optionally, in step (1), the reaction temperature is 10–35°C;

[0024] The reaction time is 0.5 to 6 hours.

[0025] Optionally, in step (1), the temperature of the reaction is independently selected from any value of 10°C, 15°C, 20°C, 25°C, 30°C, 35°C or any range between two of them.

[0026] Optionally, the reaction time is independently selected from any value of 0.5h, 1h, 2h, 3h, 4h, 5h, 6h or a range between any two.

[0027] Optionally, in step (1), the reaction is carried out at atmospheric pressure.

[0028] Optionally, step (1) specifically includes the following steps:

[0029] (a) Obtaining an aqueous solution of the copper source;

[0030] (b) Obtain an aqueous solution of the alkaline source;

[0031] (c) Obtain an aqueous solution of the reducing agent and the additive;

[0032] (d) The alkaline source aqueous solution is added to the copper source aqueous solution to produce a precipitate. Then, the reducing agent and additive mixed aqueous solution are added to react and a solid product is obtained.

[0033] Optionally, in step (a), the molar concentration of the copper source aqueous solution is 0.1 to 1.0 mol / L.

[0034] Optionally, in step (b), the molar concentration of the alkaline source aqueous solution is 0.1 to 0.5 mol / L.

[0035] Optionally, in step (2), the washing is performed using water and ethanol.

[0036] Optionally, in step (2), the drying temperature is 50–80°C;

[0037] The drying time is 3 to 24 hours.

[0038] Optionally, in step (2), the drying temperature is independently selected from any value of 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or a range between any two.

[0039] Optionally, the drying time is independently selected from any value of 3h, 5h, 10h, 15h, 20h, 22h, 24h or a range between any two.

[0040] Secondly, this application provides antioxidant spherical cuprous oxide nanoparticles prepared by the above preparation method.

[0041] Thirdly, this application provides the application of the aforementioned antioxidant spherical nano-cuprous oxide as an antibacterial material.

[0042] Compared with the prior art, this application has the following advantages:

[0043] (1) The method for preparing antioxidant spherical nano cuprous oxide provided in this application is simple to operate, and the reaction process does not require heating and pressurization, which is conducive to energy conservation and emission reduction. The reaction system is aqueous phase and the reactant is solid phase. The process is simple, and the copper source in the reactant can be completely converted into cuprous oxide. The yield is high and it is easy to scale up and produce on a large scale. The additives used are green and environmentally friendly with small dosage, and the COD content in the wastewater is low, resulting in low treatment cost. Through the synergistic effect of hydrazine hydrate and additives, the synthesized nano cuprous oxide has high crystallinity, uniform size, strong antioxidant capacity, and good antibacterial effect.

[0044] (2) The antioxidant spherical nano cuprous oxide provided in this application has a particle size that can be controlled within the range of 200 to 2000 nm. It has good crystallinity and high purity. According to HG / T 2961-2010 "Industrial Cuprous Oxide", the cuprous oxide content in the product produced by this application reaches the standard of first-grade and superior products, reaching 96.0% to 99.0%. After being placed at room temperature and pressure for 30 days, the cuprous oxide did not show any oxidation or discoloration. The cuprous oxide content was still maintained at 96.0% to 99.0% after retesting.

[0045] (3) The antioxidant spherical nanocuprous oxide prepared in this application exhibits superior antibacterial properties and can be widely used in the field of antibacterial applications. Attached Figure Description

[0046] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0047] Figure 1 The image shows a scanning electron microscope image of the nano-cuprous oxide prepared in Example 2 of this application, with a scale bar of 200 nm.

[0048] Figure 2 The image shows a scanning electron microscope (SEM) image of the nano-cuprous oxide prepared in Example 4 of this application. The scale bar is 5.00 μm.

[0049] Figure 3 The image shows a scanning electron microscope (SEM) image of the nano-cuprous oxide prepared in Example 6 of this application, with a scale bar of 5.00 μm.

[0050] Figure 4 The XRD patterns of the nano-cuprous oxide prepared in Examples 2, 4, and 6 of this application are shown below.

[0051] Figure 5 The image shows a scanning electron microscope (SEM) image of the nano-cuprous oxide prepared in Comparative Example 3 of this application. The scale bar is 1.00 μm.

[0052] Figure 6 The image shows a scanning electron microscope (SEM) image of the nano-cuprous oxide prepared in Comparative Example 4 of this application. The scale bar is 1.00 μm. Detailed Implementation

[0053] The present application is further illustrated below with reference to specific embodiments. The following descriptions are merely a few embodiments of the present application and are not intended to limit the present application in any way. Although the present application discloses preferred embodiments as follows, they are not intended to limit the present application. Any modifications or variations made by those skilled in the art without departing from the scope of the technical solution of the present application using the disclosed technical content are equivalent to equivalent implementation cases and all fall within the scope of the technical solution.

[0054] Unless otherwise specified, the raw materials used in the embodiments of this application are all purchased commercially and used directly without any special treatment.

[0055] Unless otherwise specified, the analytical methods in the embodiments all adopt conventional instrument or equipment settings and conventional analytical methods.

[0056] Example 1

[0057] A method for preparing antioxidant spherical cuprous oxide nanoparticles, comprising the following steps:

[0058] (1) Dissolve 23.25g of copper sulfate in 150mL of deionized water and stir at 400r / min for 10min;

[0059] (2) Prepare 120 mL of sodium hydroxide solution (0.3 mol / L) and let it stand and cool to room temperature;

[0060] (3) Prepare 120 mL of a mixed solution of hydrazine hydrate (5 mL), glucose (0.1 g), and sucrose (0.05 g);

[0061] (4) Add sodium hydroxide solution to copper acetate solution to produce a blue precipitate. After increasing the stirring rate to disperse the precipitate evenly, quickly add a mixed solution of hydrazine hydrate, glucose and sucrose. Stir at 25°C for 1 hour to obtain a solid product.

[0062] (5) The solid product was washed twice with deionized water and once with ethanol, and then dried in an oven at 70°C for 6 hours to obtain orange-red cuprous oxide.

[0063] Example 2

[0064] A method for preparing antioxidant spherical cuprous oxide nanoparticles, comprising the following steps:

[0065] (1) Add 32g of copper sulfate to 150mL of deionized water and stir at 400r / min for 10min;

[0066] (2) Prepare 120 mL of sodium hydroxide solution (0.3 mol / L) and let it stand and cool to room temperature;

[0067] (3) Prepare 60 mL of aqueous solution of hydrazine hydrate (5 mL) and 60 mL of mixed aqueous solution of sucrose (0.12 g) and sodium citrate (0.03 g);

[0068] (4) Add sodium hydroxide solution to copper sulfate solution to produce a blue precipitate. After the precipitate is dispersed evenly by increasing the stirring rate, add hydrazine hydrate solution quickly. After reacting for 10 min, add a mixed solution of sucrose and sodium citrate. Stir at 25°C for 3 h to obtain a solid product.

[0069] (5) The solid product was washed twice with deionized water and once with ethanol, and then dried in an oven at 80°C for 3 hours to obtain orange-red cuprous oxide.

[0070] Example 3

[0071] A method for preparing antioxidant spherical cuprous oxide nanoparticles, comprising the following steps:

[0072] (1) Dissolve 23.25g of copper acetate in 150mL of deionized water and stir at 400r / min for 10min;

[0073] (2) Prepare 120 mL of sodium carbonate solution (0.3 mol / L) and let it stand and cool to room temperature;

[0074] (3) Disperse sodium acetate (0.05g) in 120mL of deionized water, stir well, and then add hydrazine hydrate (5mL);

[0075] (4) Add sodium carbonate solution to copper acetate solution to produce blue precipitate. Increase the stirring rate to disperse the precipitate evenly and then quickly add it to a mixed solution of hydrazine hydrate and sodium acetate. Stir the reaction at 25°C for 2 hours and centrifuge to obtain solid product.

[0076] (5) The solid product was washed twice with deionized water and once with ethanol, and then dried in an oven at 50°C for 24 hours to obtain brick-red cuprous oxide.

[0077] Example 4

[0078] A method for preparing antioxidant spherical cuprous oxide nanoparticles, comprising the following steps:

[0079] (1) Add 32g of copper acetate to 150mL of deionized water and stir at 400r / min for 10min;

[0080] (2) Prepare 120 mL of potassium hydroxide solution (0.3 mol / L) and let it stand and cool to room temperature;

[0081] (3) Disperse sodium acetate (0.28g) in 120mL of deionized water, stir well, and then add hydrazine hydrate (5mL);

[0082] (4) Add potassium hydroxide solution to copper sulfate solution to produce blue precipitate. After increasing the stirring rate to disperse the precipitate evenly, quickly add a mixed solution of hydrazine hydrate and sodium acetate. Stir the reaction at 25°C for 1 hour and centrifuge to obtain solid product.

[0083] (5) The solid product was washed twice with deionized water and once with ethanol, and then dried in an oven at 60°C for 6 hours to obtain brick-red cuprous oxide.

[0084] Example 5

[0085] A method for preparing antioxidant spherical cuprous oxide nanoparticles, comprising the following steps:

[0086] (1) Dissolve 15.82g of copper chloride in 150mL of deionized water and stir at 400r / min for 10min;

[0087] (2) Prepare 120 mL of sodium hydroxide solution (0.3 mol / L) and let it stand and cool to room temperature;

[0088] (3) Disperse starch (0.04 g) and hydrazine hydrate (5 mL) evenly in 60 mL of deionized water;

[0089] (4) Add sodium hydroxide solution to copper carbonate solution to produce blue precipitate. After the precipitate is dispersed evenly by increasing the stirring rate, add hydrazine hydrate dispersion immediately. After reacting for 10 min, add starch solution and react at 25℃ for 0.5 h.

[0090] (5) The solid product was washed twice with deionized water and once with ethanol, and then dried in an oven at 60°C for 10 hours to obtain brick-red cuprous oxide.

[0091] Example 6

[0092] A method for preparing antioxidant spherical cuprous oxide nanoparticles, comprising the following steps:

[0093] (1) Dissolve 15.82g of copper chloride in 150mL of deionized water and stir at 400r / min for 10min;

[0094] (2) Prepare 120 mL of ammonia solution (0.5 mol / L) and let it stand and cool to room temperature;

[0095] (3) Prepare 60 mL of hydrazine hydrate (5 mL) and sodium acetate (0.07 g) solutions respectively;

[0096] (4) Add ammonia solution to copper carbonate solution to produce blue precipitate. After increasing the stirring rate to disperse the precipitate evenly, add hydrazine hydrate dispersion immediately. After reacting for 10 min, add sodium acetate solution and react at 25℃ for 2 h.

[0097] (5) The solid product was washed twice with deionized water and once with ethanol, and then dried in an oven at 60°C for 10 hours to obtain brick-red cuprous oxide.

[0098] Comparative Example 1

[0099] A method for preparing nano-cuprous oxide comprises the following steps:

[0100] (1) Add 32g of copper sulfate to 150mL of deionized water and stir at 400r / min for 10min;

[0101] (2) Prepare 120 mL of sodium hydroxide solution (0.3 mol / L) and let it stand and cool to room temperature;

[0102] (3) Disperse hydrazine hydrate (5 mL) in 120 mL of deionized water and stir until well mixed;

[0103] (4) Add sodium hydroxide solution to copper sulfate solution to produce blue precipitate. After increasing the stirring rate to disperse the precipitate evenly, quickly add hydrazine hydrate dispersion and stir the reaction at 25°C for 1 hour. Centrifuge to obtain solid product.

[0104] (5) The solid product was washed twice with deionized water and once with ethanol, and then dried in an oven at 70°C for 6 hours to obtain nano-cuprous oxide.

[0105] Comparative Example 2

[0106] A method for preparing nano-cuprous oxide comprises the following steps:

[0107] (1) Add 32g of copper sulfate to 150mL of deionized water and stir at 400r / min for 10min;

[0108] (2) Prepare 120 mL of sodium hydroxide solution (0.3 mol / L) and let it stand and cool to room temperature;

[0109] (3) Disperse glucose (0.1g) and sucrose (0.05g) in 120mL of deionized water and stir well;

[0110] (4) When sodium hydroxide solution is added to copper sulfate solution, a blue precipitate is produced. After the precipitate is dispersed evenly by increasing the stirring rate, a dispersion of glucose and sucrose is quickly added. The mixture is stirred at 25°C for 1 hour and no obvious changes are observed.

[0111] Comparative Example 3

[0112] A method for preparing nano-cuprous oxide comprises the following steps:

[0113] (1) Add 32g of copper sulfate to 150mL of deionized water and stir at 400r / min for 10min;

[0114] (2) Prepare 120 mL of sodium hydroxide solution (0.3 mol / L) and let it stand and cool to room temperature;

[0115] (3) Prepare 120 mL of ascorbic acid (10.6 g) solution;

[0116] (4) Add sodium hydroxide solution to copper sulfate solution to produce a blue precipitate. After the precipitate is dispersed evenly by increasing the stirring rate, add ascorbic acid dispersion immediately and react at 25°C for 1 hour.

[0117] (5) The solid product was washed twice with deionized water and once with ethanol, and then dried in an oven at 60°C for 11 hours to obtain dark red cuprous oxide.

[0118] Comparative Example 4

[0119] A method for preparing nano-cuprous oxide comprises the following steps:

[0120] (1) Add 32g of copper sulfate to 150mL of deionized water and stir at 400r / min for 10min;

[0121] (2) Prepare 120 mL of sodium hydroxide solution (0.3 mol / L) and let it stand and cool to room temperature;

[0122] (3) Prepare 120 mL of a mixed solution of ascorbic acid (10.6 g), glucose (0.1 g), and sucrose (0.05 g);

[0123] (4) Add sodium hydroxide solution to copper sulfate solution to produce blue precipitate. After the precipitate is dispersed evenly by increasing the stirring rate, immediately add a mixed solution of ascorbic acid, glucose and sucrose and react at 25°C for 1 hour.

[0124] (5) The solid product was washed twice with deionized water and once with ethanol, and then dried in an oven at 60°C for 15 hours to obtain brick-red cuprous oxide.

[0125] Experimental Example 1

[0126] The scanning electron microscope (SEM) images of the nano-cuprous oxide obtained in Comparative Examples 3 and 4 are shown below. Figure 5 and Figure 6 As shown, all particles are cubic with a diameter of 1–1.5 μm and are relatively uniform.

[0127] Scanning electron microscope (SEM) images of the nano-cuprous oxide obtained in Examples 2, 4, and 6 are shown below. Figure 1 , Figure 2 and Figure 3 As shown, the particle size is between 200 and 2000 nm, and the particles are relatively uniform. The XRD patterns of cuprous oxide obtained in Examples 2 (also known as Example 2), 4 (also known as Example 4), and 6 (also known as Example 6) are shown below. Figure 4 As shown, the diffraction peaks of the nano-cuprous oxide completely correspond to the diffraction peaks of the standard card of Cu2O PDF#05-0667, and the characteristic peaks of XRD are quite obvious, indicating that the prepared cuprous oxide has a high degree of crystallinity.

[0128] Experiment Example 2

[0129] Comparative experiment on the antioxidant effects of cuprous oxide:

[0130] Taking Example 1 and Comparative Example 1 as examples, the specific test data results are shown in Table 1.

[0131] Table 1 Comparison of cuprous oxide content and color before and after 30 days.

[0132]

[0133] Note: L represents brightness, a represents red and green, b represents blue and yellow, and * represents relative value.

[0134] The cuprous oxide content and color of the two methods synthesized before and after 30 days of storage were tested. As shown in Table 1, compared with Comparative Example 1, the cuprous oxide content and color values ​​of Example 1 of this application did not change significantly, showing excellent antioxidant and color-changing properties.

[0135] Experimental Example 3

[0136] Antibacterial performance test:

[0137] Antibacterial performance was tested according to Appendix A of GB / T 21510-2008 "Test Methods for Antibacterial Properties of Nano-Inorganic Materials". Test strains: Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 6538, and Candida albicans ATCC10231. Test samples: Cuprous oxide powder prepared according to Example 2 and its residue after 30 days of storage. The verification results are shown in Table 2.

[0138] Table 2 Antibacterial properties of cuprous oxide

[0139]

[0140]

[0141] As shown in Table 2, the cuprous oxide powder prepared in Example 2 and the sample after 30 days of storage all showed antibacterial rates of >99.9% against Staphylococcus aureus, Escherichia coli, and Candida albicans. This indicates that the cuprous oxide prepared in this application has excellent antibacterial properties, and the cuprous oxide still maintains good antibacterial effect after 30 days of storage.

[0142] The antibacterial properties of polyester fabrics with added cuprous oxide were tested according to GB / T 20944.2-2007 "Evaluation of antimicrobial properties of textiles - Part 2: Absorption method". The bacterial strain used in the test was *Escherichia coli* ATCC8099. Cuprous oxide prepared according to the methods of Examples 2, 4, and 6 was added to the polyester fabric, and the antibacterial test results are shown in Table 3.

[0143] Table 3. Antibacterial performance test of polyester fabrics with added cuprous oxide.

[0144] Example 2 24h 2.5 >99% Example 4 24h 2.4 >99% Example 6 24h 2.5 >99%

[0145] As shown in Table 3, the fabrics containing Examples 2, 4, and 6 were irradiated with ultraviolet light for 30 minutes, then inoculated with bacterial solution, and cultured for 24 hours. The measured inhibition values ​​were 2.5, 2.4, and 2.5, respectively, with inhibition rates all >99%. According to the evaluation standard of antibacterial effect in GB / T 20944.2-2007, when the inhibition value is ≥2 or the inhibition rate is ≥99%, the sample has a good antibacterial effect.

[0146] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and all fall within the scope of the technical solution.

Claims

1. A method for preparing antioxidant spherical cuprous oxide nanoparticles, characterized in that, Includes the following steps: (1) First, obtain a copper source aqueous solution, then obtain an alkaline source aqueous solution, and then obtain a mixed aqueous solution of reducing agent and additive; add the alkaline source aqueous solution to the copper source aqueous solution to produce a precipitate, accelerate the stirring rate to make the precipitate disperse evenly, then add the mixed aqueous solution of reducing agent and additive, and react at 10~35℃ and normal pressure for 0.5~6h to obtain a solid product; (2) The solid product is washed with water and ethanol and then dried at 50-80°C for 3-24 hours to obtain the antioxidant spherical nano cuprous oxide; In step (1), the reducing agent is hydrazine hydrate; The additives include at least one of glucose, sucrose, starch, sodium citrate, and sodium acetate. The molar ratio of the copper source to the additive is 20~100:1, wherein the number of moles of the copper source is calculated based on the number of moles of copper ions, and the number of moles of the additive is calculated based on the number of moles of the substance itself. The molar concentration of the copper source aqueous solution is 0.1~1.0 mol / L; The molar concentration of the alkaline source aqueous solution is 0.1~0.5 mol / L.

2. The method for preparing antioxidant spherical cuprous oxide nanoparticles according to claim 1, characterized in that, In step (1), the molar ratio of the copper source to the reducing agent is 1:0.25~1, wherein the number of moles of the copper source is calculated based on the number of moles of copper ions, and the number of moles of the reducing agent is calculated based on the number of moles of the substance itself.

3. The method for preparing antioxidant spherical cuprous oxide nanoparticles according to claim 1, characterized in that, In step (1), the copper source is a divalent copper source; The divalent copper source includes copper sulfate, copper acetate, copper nitrate, or copper chloride.

4. The method for preparing antioxidant spherical cuprous oxide nanoparticles according to claim 1, characterized in that, In step (1), the alkali source includes sodium hydroxide, potassium hydroxide, ammonia or sodium carbonate.

5. The preparation method according to any one of claims 1 to 4, characterized in that, The particle size of the antioxidant spherical nano cuprous oxide is 200~2000nm; its cuprous oxide content is 96.0~99.0% as determined by HG / T 2961-2010 "Industrial Cuprous Oxide", and the cuprous oxide content remains at 96.0~99.0% after being placed at room temperature and pressure for 30 days.

Citation Information

Patent Citations

  • Cuprous oxide micron hollow sphere, its synthetic method and application method

    CN103395822A

  • Preparation method of micro-nano cuprous oxide particles with controllable morphology and size

    CN104261457A

  • Preparation and application of copper oxide nanometer hollow spheres

    CN104692445A